IDENTIFICATION OF IRON TOLERANT CANDIDATE LOCI IN RICE DETERMINED THROUGH GENOME-WIDE ASSOCIATION STUDY - Dwinita Wikan Utami, M.Si.; Ida Rosdianti; Lili Chrisnawati; Subardi Subardi; Siti Nurani; Suwarno Suwarno (Indonesian Agency for Agricultural Research and Development, 2020)
Iron (Fe) toxicity is a significant abiotic stress in swamp land. The study aimed to identify the candidate loci related to Fe toxicity tolerance through Genome-Wide Association Study (GWAS) approach. The study used 288 rice accessions consisting of 192 breeding lines and 50 local landraces, and custom-designed 384 rice SNPs-chips. A field evaluation was conducted in inland swamp for two season periods (2014 and 2015). Phenotypic data and association mapping were analyzed using XLSTAT and TASSEL 3.0. The candidate loci were analyzed by functional gene detection of the significant SNPs aligned to the Rice Annotation Project and the Institute for Genomic Research databases. Three linkage disequilibrium (LD) blocks were detected in the Fe tolerant population around the significant SNPs. The first LD block was mapped in chromosome 1 (the AtIRT gene and qFETOX1; qFETOX1-3 QTLs loci) resembled partitioning of Fe-toxicity tolerant mechanism. The second LD blocks located in chromosome 2 (qFE-TOX-2-1 and qFETOX-2 QTLs loci) and chromosome 3 (qFETOX-3 QTL, OsNAS1 and OsNAS2 loci), probably contributed to Fe exclusion mechanism. The third LD blocks located in chromosome 4 (OsFRO2 and qFETOX-4 QTL loci) and chromosome 7 (OsIRT2 and NAS3 loci). The third LD block found on tolerant genotypes both on vegetative and generative stages. This condition indicated that these loci were presumed playing a role for Fe toxicity tolerance in rice. Result of the study are beneficial for determining the strategy on developing Fe-toxicity tolerant rice for specific swamp land type through breeding programs.